2021
DOI: 10.3390/ijms222413377
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic NRAS Accelerates Rhabdomyosarcoma Formation When Occurring within a Specific Time Frame during Tumor Development in Mice

Abstract: In the Ptch+/- mouse model for embryonal rhabdomyosarcoma (ERMS), we recently showed that oncogenic (onc) H-, K- or NRAS mutations do not influence tumor growth when induced at the advanced, full-blown tumor stage. However, when induced at the invisible ERMS precursor stage at 4 weeks of age, tumor development was enforced upon oncHRAS and oncKRAS but not by oncNRAS, which instead initiated tumor differentiation. These data indicate that oncRAS-associated processes differ from each other in dependency on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moreover, ectopic mouse models did not recapitulate any of the human anatomical tumor sites, thus having very limited translational value. While orthotopic mouse models recapitulated the limb RMS phenotype, a variety of additional tumor locations were observed merely in GEMM systems within our study cohort, including the abdomen, back, head/neck, rib cage, pelvis, body wall, and tongue (19,20,27,(64)(65)(66)(67)(68)(69)(70).…”
Section: From Bedside To Benchmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, ectopic mouse models did not recapitulate any of the human anatomical tumor sites, thus having very limited translational value. While orthotopic mouse models recapitulated the limb RMS phenotype, a variety of additional tumor locations were observed merely in GEMM systems within our study cohort, including the abdomen, back, head/neck, rib cage, pelvis, body wall, and tongue (19,20,27,(64)(65)(66)(67)(68)(69)(70).…”
Section: From Bedside To Benchmentioning
confidence: 88%
“…Ragab el. showed that induction of the oncNRAS mutation in 2-week-old Ptch+/-NRasfl/+ mice (GEMM) accelerates eRMS formation compared to 4-week-old mice (68). The other studies utilized mice of different ages, including 3-week-old mice (86), mice between 4 to 8 weeks (87, 88), 6 to 8 weeks (41,89), or 8 to 12 weeks (90,91), irrespective of the mouse model subtype.…”
Section: Patient´s Agementioning
confidence: 99%